Aging of polymers, polymer blends, and polymer composites - Zaikov, G. E. 1935-; Bouchachenko, A. L. (Anatoli L.); Ivanov, V. B. (Viktor Borisovich) (New York : Nova Science Publishers)
Includes bibliographical references and indexes